A nano-cocrystal strategy to improve the dissolution rate and oral bioavailability of baicalein - Jiaxin Pi; Shuya Wang; Wen Li; Dereje Kebebe; Ying Zhang; Bing Zhang; Dongli Qi; Pan Guo; Nan Li; Zhidong Liu (Elsevier, 2019)
Baicalein (BE) is one of the main active flavonoids representing the variety of pharmacological effects including anticancer, anti-inflammatory and cardiovascular protective activities, but it's very low solubility, dissolution rate and poor oral absorption limit the therapeutic applications. In this work, a nano-cocrystal strategy was successfully applied to improve the dissolution rate and bioavailability of BE. Baicalein-nicotinamide (BE-NCT) nano-cocrystals were prepared by high pressure homogenization and evaluated both in vitro and in vivo. Physical characterization results including scanning electron microscopy, dynamic light scattering, powder X-ray diffraction and differential scanning calorimetry demonstrated that BE-NCT nano-cocrystals were changed into amorphous state with mean particle size of 251.53 nm. In the dissolution test, the BE-NCT nano-cocrystals performed 2.17-fold and 2.54-fold enhancement than BE coarse powder in FaSSIF-V2 and FaSSGF. Upon oral administration, the integrated AUC0 − t of BE-NCT nano-cocrystals (6.02-fold) was significantly higher than BE coarse powder (1-fold), BE-NCT cocrystals (2.87-fold) and BE nanocrystals (3.32-fold). Compared with BE coarse powder, BE-NCT cocrystals and BE nanocrystals, BE-NCT nano-cocrystals possessed excellent performance both in vitro and in vivo evaluations. Thus, it can be seen that nano-cocrystal is an appropriate novel strategy for improving dissolution rate and bioavailability of poor soluble natural products such as BE. Keywords: Baicalein, Nano-cocrystals, Cocrystals, Bioavailability